The global prevalence, formation, and evolutionary inference of bacteria co-carrying the blaNDM and mcr resistance genes - Wang, Boqian; Li, Kexin; Chen, Mingliang; Fu, Jingjing; Zhang, Rui; Liu, Wanqiu; Wang, Yuxin; Peng, Zhixi; Buaijier, Aimaiti; Zhao, Xinru; Song, Hongbin; Ren, Hongguang; et al. (Frontiers in Microbiology, 2025)
IntroductionThe global dissemination of bacteria harboring blaNDM and mcr genes, which confer co-resistance to carbapenem and polymyxin antibiotics, poses a catastrophic threat to public health due to the ineffectiveness of last-line antibiotics.MethodsThis study integrated epidemiological and genetic analysis of 1,156 bacterial genomes from global databases and our de novo sequencing.ResultsWe demonstrate that the current “human-animal-environment” transmission drives their rapid geographical expansion and dynamic succession of dominant bacterial lineages (predominantly Escherichia, Enterobacter, and Klebsiella) over time. Notably, we identified several pieces of evolutionary evidence to elucidate the genetic dynamics of co-resistant bacterial formation as well as related plasmids and chromosome fusion. Additionally, we find that both broad-host and narrow-host plasmids are closely associated with these phenomena, but possess distinct genetic functions.DiscussionThese findings elucidate the urgency of region-tailored surveillance, highlighting the need to target high-risk plasmid types and restrict non-therapeutic antibiotic use in agriculture to delay the “no-drug-available” crisis.